Clinical presentation and outcome of fistula in ano cases - Yadu, Shruti; Toppo, Aradhana (International Surgery Journal, 2018)
Background: Fistula-in-ano is an abnormal communication between the anal canal or rectum and the perianal skin, which causes a chronic inflammatory response. The most common cause is nearly always by a previous anorectal abscess. The chief complaint of anorectal fistula is intermittent or constant drainage or discharge. There is usually a history of previous pain, swelling and recurrent abscess that ruptured spontaneously or was surgically drained. There may be a pink or red elevation exuding pus, or it may have healed. Digital rectal examination remains the main stay of diagnosis in anorectal fistula cases. Methods: The present cross sectional observational prospective study was conducted in 50 patients who presented with their complaints to the Surgery Outpatient Department and who were admitted under the Department of Surgery, Dr. B.R.A.M. Hospital, Raipur (C.G.), India during study period was from March 2015 to September 2016. Detailed clinical history and examination of the patient was recorded. All investigations relevant to the study were done in all the patients. Appropriate surgical management were performed. Postoperative findings were noted. Results: 36% patients are in the age group of 41-50. 82% are male patients and 18% patients are female patient. 76% Patients had single opening. 74% Patients had perianal discharge while 66% patients presented with perianal pain. 40% patients had h/o perianal abscess. Most common mode of presentation was discharge. 76% patients had posterior opening while 24% patients had anterior opening. Fistulectomy and fistulotomy were performed in 39 subjects (78%) and 7 subjects (14 %) respectively. Conclusions: Anal fistula is a common disease which is devastating to the patients and imposes challenges to the surgeon. Early diagnosis and appropriate management are the key to success.